Short Communication Steroid Estimation in Different Dental Applications: Steroids in Dental Applications (Biological Sciences - PJSIR, 2009)
Study of various brands of regular and medicated toothpastes of the local markets of Lahore and Karachi for the presence of steroids revealed the presence of synthetic steroids in medicated toothpastes only while all common, popular brands were devoid of steroids with a few exceptions.